Antiatherosclerotic Effect of Korean Red Ginseng Extract Involves Regulator of G-Protein Signaling 5. (24th December 2014) - Im, Eun Ju; Yayeh, Taddesse; Park, Sang-Joon; Kim, Seung-Hyung; Goo, Youn-Kyoung; Hong, Seung-Bok; Son, Young Min; Kim, Sung Dae; Rhee, Man Hee
Abstract : Regulator of G-protein signaling 5 (RGS5), an inhibitor of G α (q) and G α (i) activation, has been reported to have antiatherosclerosis. Previous studies showed antiatherosclerotic effect of Korean red ginseng water extract (KRGE) via multiple signaling pathways. However, potential protective effect of KRGE through RGS5 expression has not been elucidated. Here, we investigated the antiatherosclerotic effect of KRGE in vivo and in vitro and its role on RGS5 mRNA expression. Elevated levels of total cholesterol, lactate dehydrogenase (LDH), and triglyceride (TG) in western diet groups of low-density lipoprotein receptor deficient LDLr −/− mice were reversed by oral administration of KRGE. KRGE suppressed transcriptional activity of tumor necrotic factor alpha (TNF- α ), interleukin-6 (IL-6), and leptin in adipose tissue. It also potently repressed western diet-induced atheroma formation in aortic sinus. While KRGE showed reduced mRNA expression of inducible nitric oxide synthase (iNOS), cyclooxygenase-2 (COX-2), IL-1 β, IL-6, and TNF- α in LPS-stimulated RAW264.7 cells, it enhanced mRNA expression of RGS5. Moreover, RGS5 siRNA transfection of microglia cells pretreated with KRGE reversed its inhibitory effect on the expression of iNOS, COX-2, and IL-1 β mRNA. In conclusion, KRGE showed antiatherosclerotic and anti-inflammatory effects in western diet fed LDLr −/− mice and this effect could partly be mediated by RGS5 expression.